2019
DOI: 10.3920/bm2018.0135
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum DR7 alleviates stress and anxiety in adults: a randomised, double-blind, placebo-controlled study

Abstract: Probiotics have been reported to exert beneficial effects along the gut-brain axis. This randomised, double-blind and placebo-controlled human study aimed to evaluate such properties of Lactobacillus plantarum DR7 and its accompanying mechanisms in stressed adults. One hundred and eleven (n=111; DR7 n=56, placebo n=55) stressed adults were recruited based on moderate stress levels using the PSS-10 questionnaire. The consumption of DR7 (1×109 cfu/day) for 12 weeks reduced symptoms of stress (P=0.024), anxiety (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
97
0
19

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(134 citation statements)
references
References 36 publications
6
97
0
19
Order By: Relevance
“…For instance, it has been shown that chronic stress significantly increases gut microbiota diversity in antibiotic-treated mice and can neutralize not only stress-inducing anhedonia phenotypes but also the levels of inflammatory markers, suggesting that the development of susceptibility to stress in mice is subjected to the composition of the gut microbiota 93 . Recently, evidence has also confirmed that the use of commensal bacteria strain to improve psychological functions and cognitive health in stressed adult subjects 58 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For instance, it has been shown that chronic stress significantly increases gut microbiota diversity in antibiotic-treated mice and can neutralize not only stress-inducing anhedonia phenotypes but also the levels of inflammatory markers, suggesting that the development of susceptibility to stress in mice is subjected to the composition of the gut microbiota 93 . Recently, evidence has also confirmed that the use of commensal bacteria strain to improve psychological functions and cognitive health in stressed adult subjects 58 .…”
Section: Discussionmentioning
confidence: 91%
“…The role of gut microbiota depletion in anxiety, however, is controversial with studies describing a reduction of anxiety-like behaviours 25 , 55 , no effect 20 , 26 or an anxiolytic effect following microbiota depletion 16 . Firmicutes, Actinobacteria and Bacteroides are known to affect anxiety levels, with lower abundance being associated with elevated anxiety-like behaviour in rodents and humans 36 , 56 58 . The stronger effect observed in ABX adolescence mice over adults may also have been influenced by sex hormones peaking during adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…The emerging consumer interest in probiotics as a supplement to promote health and well-being has further propelled microbiome studies in zebrafish. The lactic acid bacteria L. plantarum is of particular interest and is currently commercialised as a beneficial probiotic that alleviates stress and anxiety in humans (Chong et al, 2019). In zebrafish, L. plantarum protects against stress-induced dysbiosis of the gut microbiota and ameliorates anxiety-related behaviour.…”
Section: Zebrafish As a Model To Study The Intestinal Microbiomementioning
confidence: 99%
“…, Burgos, Ray, & Arias, 2017.The mammalian and zebrafish gut microbiome share six bacterial divisions, but the human GI tract is primarily dominated by Firmicutes, Bacteroidetes, and Actinobacteria whereas Proteobacteria are the predominant phylum in zebrafish(Bates et al, 2006;Eckburg et al, 2005;Rawls et al, 2004). The lactic acid bacteria L. plantarum is of particular interest and is currently commercialised as a beneficial probiotic that alleviates stress and anxiety in humans(Chong et al, 2019). The successful colonisation of the larval gut with anaerobic species, including Lactobacillus paracasei and strict anaerobes such as Eubacterium limosum and Akkermansia muciniphila, in particular, was an important stepping stone in establishing zebrafish as a surrogate host for studies on the human gut microbiome (Arias-Jayo et al, 2018; Toh et al, 2013).The emerging consumer interest in probiotics as a supplement to promote health and well-being has further propelled microbiome studies in zebrafish.…”
mentioning
confidence: 99%
“…To authors' knowledge, the linkage among virulence factors, proinflammatory cytokines, and probiotics is a first report, which could be a novel action mechanism for probiotics. L. plantarum DR7 reduced proinflammatory cytokines, such as interferon-γ and transforming growth factor-α, but increased plasma anti-inflammatory cytokine IL-10 in stressed adults ( Chong et al., 2019 ). Serum levels of proinflammatory cytokines IL-1β, IL-2, IL-6, IFN-γ, and anti-inflammatory IL-4, IL-10 changed linearly or quadratically both at the initial and final phases of broilers fed with E. faecium NCIMB 11181 ( Wu et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%